Spatial and temporal evaluation of groundwater hydrochemistry in an active phreatic zone of developed basin in Selangor, Malaysia - Zainudin, ‘Afiatul Mar'iyah; Zulkefli, Syahirah Nasuha; Looi, Ley Juen; Aris, Ahmad Zaharin; Sefie, Anuar; Mohd Isa, Noorain (Elsevier, 2023)
Groundwater provides freshwater supply for multiple purposes such as drinking water, irrigation, and industrial processes. Due to intensive developments, contaminants from various land use practices infiltrate into the groundwater system and jeopardized the existing quality. Besides, uncontrolled groundwater extraction exacerbate the existing issue due to improper management and uncontrolled extraction; especially in developing areas. This study centralized in Kuala Langat; an urbanized basin with mix of land use practices (residential, industrial, and agricultural) with the aim to observe the impacts of land use activities towards groundwater hydrochemistry on seasonal and temporal scale. A total of 30 groundwater samples were collected along Langat River Basin to assess the physicochemical parameters, concentration of major ions and heavy metals. Application of multivariate and graphical analysis as well as pollution indices were incorporated in this study to evaluate the degree of heavy metals contamination. The order of cations concentration evaluated in pre- and post-monsoon seasons are Na > Ca > K > Mg and Na > Mg > Ca > K, respectively while the order of anions concentration is HCO3>Cl > SO4 for both monsoon seasons. Both calculated HPI and Cd value suggested that agricultural activity is the main contributor for groundwater pollution. Overall, most of the stations are potable to be consumed as stated from HPI and Cd results except for station SSG10. It is suggested that for a better precaution, the groundwater in Langat River Basin shall undergo prior treatment before further consumption.